Defectos refractivos y su efecto en la calidad visual en adolescentes de la Iglesia Cristiana Elohim. Ventanas. Octubre 2024 – abril 2025. - Cedeño Canteral, Jennifer Gabriela (2025)
In adolescents, the topic of visual health is of total interest due to the degrees worldwide reaching figures of more than 314 million individuals with refractive errors such as myopia, hyperopia and astigmatism, of this figure the 153 million with refractive errors are not corrected, having an impact on the social development and visual quality of the adolescent. In our country Ecuador, the lack of data on the prevalence of refractive errors makes this topic of total interest, which is why it led us to carry out our study at the Elohim Christian Church in Ventanas. The present study not only sought to identify the types of refractive errors present in adolescents, but also sought to demonstrate how these defects affect their visual quality, which can be improved with optical corrections. The study was justified by the need to address uncorrected refractive errors, and as a hypothesis it was proposed that refractive errors negatively impact visual quality. The study was crucial to initiate intervention programs that provide comprehensive development in adolescents of the Elohim Christian Church, highlighting the importance of regular check-ups as prevention of long-term visual problems.